PENGENALAN PERBANKAN SYARIAH MELALUI BAKTI SOSIAL DI DESA CIASMARA, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Syafira Laras Balqis; Tubagus Rifqy Thantawi; Miftakhul Anwar (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract The Covid-19 socialization and social service activities are community service activities in an effort to help the community to meet the needs of life and solve problems experienced by the community, especially in dealing with the transmission of Covid-19. The activity was carried out through the Covid-19 Socialization and Social Service program which is a community service-based activity to increase public knowledge about efforts to break the chain of transmission of Covid-19 carried out at Rt. 1, 2 and 3 in the Ciasmara sub-district, Pamijahan District, Bogor, West Java, with service methods in the form of counseling activities, demonstrations, distribution of masks and how to make Handsanitizer and spraying disinfectants in the residential environment. The results show a positive response from the government and high active community participation. Keywords: community service, covid-19, community participation